Sweet's syndrome associated with Crohn's disease - Caren dos Santos Lima; Roberta Duarte Bezerra Pinto; Heliana Freitas de Oliveira Góes; Simone de Abreu Neves Salles; Enoi Aparecida Guedes Vilar; Carla dos Santos Lima (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Sweet's syndrome is an uncommon benign skin disorder, whose pathogenesis remains unknown. Its classic form is more common in women and presents itself as papular-nodular, painful and erythematous or violaceous lesions. It mainly affects the face, neck, and upper limbs. Fever and neutrophilic leukocytosis are also common features. Although it is considered a systemic disease marker in more than half of patients, the association of this condition with Crohn's disease is rare, with few cases reported in the literature, of which, none in Brazil. We report the case of a patient with Crohn's disease who developed the classical features of Sweet's syndrome.